A kind of ferroaluminate cement water reducing agent and preparation method thereof
By grafting modification of β-cyclodextrin, a polycarboxylic acid water reducer containing zwitterion and cyclodextrin was prepared, which solved the problem that the existing iron aluminate cement water reducer in a high mud-containing sand and gravel environment The problem of inadequacy is shown below, and the effect of improving the fluidity and compressive strength of cement slurry is achieved.
Patent Information
- Application Number
- CN202411402245.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing iron aluminate cement water reducing agents show discomfort in high mud and sand environments, resulting in a decrease in water reduction rate and fluidity, affecting construction efficiency and quality.
By grafting modification of β-cyclodextrin, a polycarboxylic acid water reducing agent containing zwitterionic and cyclodextrin was prepared, and maleic anhydride modified β-cyclodextrin and methoxy polyethylene dichloride were used to modify β-cyclodextrin and methyloxy polyethylene dichloride. Alcohol acrylate, etc. are esterified and polymerized to obtain unsaturated zwitterionic cyclodextrin, and finally polymerized with maleic anhydride and acrylic acid to prepare a ferric acid cement water reducing agent.
The improved water reducing agent significantly improves the adaptability to cement, delays the hydration process of cement, enhances the slump retention ability, improves the fluidity and compressive strength of the cement slurry, and the preparation process is simple and controllable, suitable for Industrialized production.
Smart Images

Figure BDA0005075601320000051 
Figure BDA0005075601320000053 
Figure BDA0005075601320000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a ferroaluminate cement water reducer and a preparation method thereof. Background Art
[0002] Ferroaluminate cement is made of ferrous materials, bauxite and silicate raw materials. The calcined cement clinker with anhydrous calcium sulphoaluminate, dicalcium silicate and calcium aluminoferrite as the main mineral components is mixed with appropriate amounts of limestone and gypsum and ground together. It has the characteristics of early strength, frost resistance and low energy consumption, and is gradually used in civil engineering. However, the mineral composition of ferroaluminate cement clinker also determines the shortcomings of this type of cement, such as fast hydration and hardening and short setting time, which leads to the phenomenon of rapid decrease in fluidity of the slurry, and sometimes even fails to meet basic construction requirements, bringing great inconvenience to construction operations. In order to make ferroaluminate cement obtain better workability and construction time while ensuring strength, chemical admixtures are often used to adjust it in actual applications.
[0003] Water reducer is one of the most widely used admixtures in cement concrete. The role of water reducer is to improve the working performance and strength of concrete by reducing the water consumption of concrete mixture without changing the slump of concrete. For ferroaluminate cement, adding an appropriate amount of water reducer can effectively delay its hardening speed, thereby providing more operating space for construction personnel and improving construction efficiency and quality. In the prior art, water reducing effect is generally exerted by adding polycarboxylic acid water reducer to cement. It is mainly prepared by free radical copolymerization of unsaturated carboxylic acid and unsaturated active polyether polyethylene glycol long chain. Its basic structural characteristics are that the main chain is aliphatic alkane, distributed with one or more ionic groups, and the side chain is composed of hydrophilic polyoxyalkylene polyethylene glycol long chain. However, the disadvantage is that it is not adaptable to cement and is sensitive to the mud content in sand and gravel. When the mud content in sand and gravel is greater than 5%, its water reduction rate and fluidity decrease significantly, and plasticity decreases rapidly. This may be because the mud in the sand and gravel seriously weakens the dispersibility of polycarboxylic acid water reducer on cement, thereby affecting its promotion and use.
[0004] β-cyclodextrin polycarboxylic acid water reducer has good dispersibility due to the introduction of high steric hindrance functional group β-cyclodextrin. Patent CN104817663B provides a functional monomer containing β-cyclodextrin. β-cyclodextrin, p-toluenesulfonyl chloride, alcohol amine and glycidyl ester are used as raw materials. A modified β-cyclodextrin functional monomer is synthesized through selective sulfonylation reaction, alcohol amine substitution reaction and epoxy ring-opening reaction. The monomer is used to react with acrylic acid, sodium methacrylic acid and isobutylene alcohol polyoxyethylene ether to carry out free radical polymerization to prepare a polycarboxylic acid water reducer containing β-cyclodextrin in the side chain. However, the preparation method is not suitable for the preparation of polycarboxylic acid water reducer. The prepared water-reducing agent has a relatively simple and fixed molecular structure, and requires multiple monomers to participate in the reaction. The chemical reaction is complex, and it is difficult to meet the requirements of safe production and energy conservation and environmental protection. The product quality is also difficult to guarantee, and the economic cost is high; since the β-cyclodextrin molecule contains multiple reaction sites, it is difficult to introduce a monoolefin double bond, and the preparation of the β-cyclodextrin monomer is relatively difficult; therefore, it is urgent to improve the polycarboxylic acid water-reducing agent itself, and at the same time, the preparation process of the polycarboxylic acid water-reducing agent needs to be simple and easy to control. The present application prepares a polycarboxylic acid water-reducing agent containing zwitterions and cyclodextrin by grafting modification of cyclodextrin to meet the working requirements of ferroaluminate cement. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a ferroaluminate cement water reducer and a preparation method thereof. The preparation method of the water reducer is simple, improves the working performance of ferroaluminate cement, and greatly improves the compatibility with cement.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing alumina-ferrocement water reducing agent is carried out according to the following steps:
[0008] Step (1), under a nitrogen atmosphere, add maleic anhydride modified β-cyclodextrin to a reaction flask and dissolve it in dichlorothionyl, stir at 70-85° C. for 3-8 hours, remove dichlorothionyl under reduced pressure, add N,N-dimethylformamide, stir to dissolve, add intermediate 3, react at 40-60° C. for 8-16 hours, cool to room temperature, filter, wash with ethanol, and dry to obtain unsaturated zwitterionic cyclodextrin.
[0009] Step (2), under a nitrogen atmosphere, maleic anhydride, acrylic acid, unsaturated zwitterionic cyclodextrin and deionized water are added to a microwave reactor, and after stirring evenly, ammonium persulfate is dissolved in deionized water to prepare an initiator solution, and is added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the mixture is reacted at 75-90° C. for 0.5-2 h, cooled to 30-40° C., and a sodium hydroxide aqueous solution is added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0010] Preferably, in step (1), the molar ratio of maleic anhydride-modified β-cyclodextrin to intermediate 3 is 1:1.5-2.
[0011] Preferably, in step (2), the molar ratio of maleic anhydride, acrylic acid, unsaturated zwitterionic cyclodextrin and ammonium persulfate is 1:0.2-0.4:0.05-0.25:0.008-0.015.
[0012] Preferably, the mass fraction of the sodium hydroxide aqueous solution in step (2) is 20-35%.
[0013] Preferably, the preparation method of intermediate 3 in step (1) is carried out according to the following steps:
[0014] Step S1, under a nitrogen atmosphere, add methoxy polyethylene glycol acrylate and methanol to a reaction flask, stir evenly, add N-methyl-4-methoxybenzylamine, stir to react, after the reaction is completed, concentrate under reduced pressure, wash with deionized water, and purify the organic phase by column chromatography to obtain intermediate 1.
[0015] Step S2, under a nitrogen atmosphere, add intermediate 1 and N,N-dimethylformamide to a reaction flask, stir evenly, add sodium 2-bromoethanesulfonate and triethylamine, react at 40-60° C. for 24-48 h, extract with ethyl acetate and deionized water, concentrate the organic phase, and purify by column chromatography to obtain intermediate 2.
[0016] Step S3, under a nitrogen atmosphere, add intermediate 2 and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 0-10°C for 12-24h, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain intermediate 3.
[0017] Preferably, in step S1, the molar ratio of methoxy polyethylene glycol acrylate to N-methyl-4-methoxybenzylamine is 1:(1.05-1.2).
[0018] Preferably, in step S1, the reaction temperature is 40-55° C. and the reaction time is 16-24 h.
[0019] Preferably, in step S2, the molar ratio of the intermediate 1, sodium 2-bromoethane sulfonate, and triethylamine is 1:(1.5-2.5):(2-3.2).
[0020] Preferably, in step S3, the molar ratio of intermediate 2 to boron tribromide is 1:(2.5-4).
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention allows methoxy polyethylene glycol acrylate to undergo Michael addition reaction with N-methyl-4-methoxybenzylamine, then undergoes quaternization reaction with sodium 2-bromoethane sulfonate, removes the methoxy group, utilizes the hydroxyl group in the structure of the methoxy polyethylene glycol acrylate to undergo esterification reaction with the carboxyl group in maleic anhydride-modified cyclodextrin, obtains unsaturated zwitterionic cyclodextrin, and finally undergoes polymerization reaction with maleic anhydride and acrylic acid to obtain aluminoferrocement cement water reducer.
[0023] Cyclodextrin has a hollow cylindrical structure that is "narrow at the top and wide at the bottom, hydrophobic inside and hydrophilic outside", which brings a significant steric hindrance effect to the polymer. At the same time, the hydroxyl groups in its structure can form complexes with calcium ions in cement under alkaline conditions, delaying the hydration process of cement and improving the collapse retention capacity of the water reducer; the polyethylene glycol long chain extends radially in the cement, and the sulfonic acid groups on its main chain are anchored on the positively charged cement particles, resulting in strong adsorption; quaternary ammonium salt cations can be adsorbed on the surface of negatively charged cement particles, thereby enhancing the steric hindrance effect, gradually increasing the charge density, and enhancing the electrostatic repulsion between cement particles; through the mutual synergistic effect between the groups, it is easy to adsorb on the surface of cement particles to form a double layer, and under the electrostatic repulsion and the synergistic steric hindrance force of cyclodextrin and polyethylene glycol long chains, the cement particles can achieve a better dispersion effect and improve the fluidity of cement paste.
[0024] The presence of cyclodextrin side chains and polyethylene glycol long chains affects the cement hydration process, can effectively weaken the interpenetration between water-reducing agent molecules and clay layers, exert steric repulsion, disintegrate the flocculation structure of cement particles, and make it difficult for particles to approach each other, so that the polycarboxylic acid water-reducing agent plays a good retarding and slump-preserving role; the cyclodextrin molecular chain contains a large number of hydroxyl groups, which can fill the gaps left by the hydration products, thereby enhancing the strength of cement and having a good late-stage strengthening effect on cement mortar; compared with the traditional method, the method of the present invention has common and easy-to-obtain raw materials required for the reaction, and the synthesis process is simple, controllable, efficient and convenient, which enriches the preparation method of synthetic ferroaluminate cement water-reducing agent and is easy to realize industrial production. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.
[0027] The preparation of maleic anhydride modified β-cyclodextrin is prepared according to "Preparation and Characterization of Maleic Anhydride Acylated β-cyclodextrin Pillared Zn / Al-CO3 Type Hydrotalcite" in Volume 38, Issue 3 of "Applied Chemical Industry": Add 9.9g of β-cyclodextrin and 100mL of N,N-dimethylformamide to the reaction flask, stir and dissolve, add 9.9g of maleic anhydride and 1.5g of concentrated sulfuric acid, react at 80°C for 3h, add acetone to precipitate, filter, and vacuum dry to obtain maleic anhydride modified β-cyclodextrin. The preparation reaction formula is as follows:
[0028]
[0029] Methoxy polyethylene glycol acrylate, CAS No. 32171-39-4, structural formula The molecular weight is 1000.
[0030] N-methyl-4-methoxybenzylamine, CA number is 702-24-9.
[0031] Sodium 2-bromoethane sulfonate, CAS number is 4263-52-9.
[0032] Example 1
[0033] (1) Under nitrogen atmosphere, 35 mmol of methoxy polyethylene glycol acrylate and 420 mL of methanol were added to a reaction flask, stirred evenly, and then 39.2 mmol of N-methyl-4-methoxybenzylamine was added. The mixture was reacted at 45° C. for 20 h, concentrated under reduced pressure, washed with deionized water, and the organic phase was purified by column chromatography (ethyl acetate / petroleum ether 0-25%) to obtain intermediate 1. The preparation reaction formula is as follows:
[0034]
[0035] (2) Under nitrogen atmosphere, 30 mmol of intermediate 1 and 750 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 54 mmol of sodium 2-bromoethanesulfonate and 78 mmol of triethylamine were added. The mixture was reacted at 50° C. for 35 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and purified by column chromatography (ethyl acetate / petroleum ether 10-50%) to obtain intermediate 2.
[0036] (3) Under nitrogen atmosphere, 25 mmol of intermediate 2 and 850 mL of dichloromethane were added to a reaction flask, stirred evenly, and then 80 mmol of boron tribromide was added. The mixture was reacted at 0°C for 16 h, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain intermediate 3. The preparation reaction formula is as follows:
[0037]
[0038] (4) Under nitrogen atmosphere, 20 mmol of maleic anhydride-modified β-cyclodextrin was added to a reaction flask and dissolved in 720 mL of dichlorothionyl. The mixture was stirred at 75° C. for 5 h. The dichlorothionyl was removed under reduced pressure. 900 mL of N,N-dimethylformamide was added and stirred to dissolve. 27 mmol of intermediate 3 was added and reacted at 50° C. for 12 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain unsaturated zwitterionic cyclodextrin.
[0039] (5) Under a nitrogen atmosphere, 10 mmol of maleic anhydride, 3 mmol of acrylic acid, 0.5 mmol of unsaturated zwitterionic cyclodextrin and deionized water were added to a microwave reactor. After stirring, 0.12 mmol of ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and the solution was added dropwise at a rate of 1 mL / min. After the addition was completed, the solution was reacted at 85° C. for 1 h, cooled to 35° C., and a 25% by mass sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0040] Example 2
[0041] (1) Under nitrogen atmosphere, 65 mmol of methoxy polyethylene glycol acrylate and 650 mL of methanol were added to a reaction flask. After stirring, 68.25 mmol of N-methyl-4-methoxybenzylamine was added, and the mixture was reacted at 55° C. for 16 h. The mixture was concentrated under reduced pressure and washed with deionized water. The organic phase was purified by column chromatography (ethyl acetate / petroleum ether 0-25%) to obtain intermediate 1.
[0042] (2) Under nitrogen atmosphere, 60 mmol of intermediate 1 and 1200 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 90 mmol of sodium 2-bromoethanesulfonate and 120 mmol of triethylamine were added. The mixture was reacted at 60° C. for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and purified by column chromatography (ethyl acetate / petroleum ether 10-50%) to obtain intermediate 2.
[0043] (3) Under nitrogen atmosphere, 50 mmol of intermediate 2 and 1750 mL of dichloromethane were added to a reaction flask. After stirring, 125 mmol of boron tribromide was added. The mixture was reacted at 10° C. for 12 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain intermediate 3.
[0044] (4) Under nitrogen atmosphere, 45 mmol of maleic anhydride-modified β-cyclodextrin was added to a reaction flask and dissolved in 1125 mL of thionyl chloride. The mixture was stirred at 85°C for 3 h. The thionyl chloride was removed under reduced pressure, 1800 mL of N,N-dimethylformamide was added and stirred to dissolve, 67.5 mmol of intermediate 3 was added, and the mixture was reacted at 60°C for 8 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain unsaturated zwitterionic cyclodextrin.
[0045] (5) Under a nitrogen atmosphere, 10 mmol of maleic anhydride, 2 mmol of acrylic acid, 1 mol of unsaturated zwitterionic cyclodextrin and deionized water were added to a microwave reactor. After stirring, 0.08 mmol of ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and the solution was added dropwise at a rate of 1.2 mL / min. After the addition was completed, the solution was reacted at 90° C. for 0.5 h, cooled to 40° C., and a 20% by mass sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0046] Example 3
[0047] (1) Under nitrogen atmosphere, 20 mmol of methoxy polyethylene glycol acrylate and 300 mL of methanol were added to a reaction flask. After stirring, 24 mmol of N-methyl-4-methoxybenzylamine was added. The mixture was reacted at 40° C. for 24 h, concentrated under reduced pressure, washed with deionized water, and the organic phase was purified by column chromatography (ethyl acetate / petroleum ether 0-25%) to obtain intermediate 1.
[0048] (2) Under nitrogen atmosphere, 16 mmol of intermediate 1 and 480 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 40 mmol of sodium 2-bromoethanesulfonate and 51.2 mmol of triethylamine were added. The mixture was reacted at 40° C. for 48 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and purified by column chromatography (ethyl acetate / petroleum ether 10-50%) to obtain intermediate 2.
[0049] (3) Under nitrogen atmosphere, 13 mmol of intermediate 2 and 520 mL of dichloromethane were added to a reaction flask. After stirring, 52 mmol of boron tribromide was added. The mixture was reacted at 0°C for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain intermediate 3.
[0050] (4) Under nitrogen atmosphere, 10 mmol of maleic anhydride-modified β-cyclodextrin was added to a reaction flask and dissolved in 400 mL of thionyl chloride. The mixture was stirred at 70° C. for 8 h. The thionyl chloride was removed under reduced pressure. 400 mL of N,N-dimethylformamide was added and stirred to dissolve. 15 mmol of intermediate 3 was added and reacted at 40° C. for 16 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain unsaturated zwitterionic cyclodextrin.
[0051] (5) Under a nitrogen atmosphere, 10 mmol of maleic anhydride, 4 mmol of acrylic acid, 1.5 mmol of unsaturated zwitterionic cyclodextrin and deionized water were added to a microwave reactor. After stirring, 0.15 mmol of ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and the solution was added dropwise at a rate of 0.8 mL / min. After the addition was completed, the solution was reacted at 75° C. for 2 h, cooled to 30° C., and a 35% by mass sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0052] Example 4
[0053] (1) Under nitrogen atmosphere, 42 mmol of methoxy polyethylene glycol acrylate and 525 mL of methanol were added to a reaction flask. After stirring, 46.2 mmol of N-methyl-4-methoxybenzylamine was added. The mixture was reacted at 50° C. for 18 h, concentrated under reduced pressure, washed with deionized water, and the organic phase was purified by column chromatography (ethyl acetate / petroleum ether 0-25%) to obtain intermediate 1.
[0054] (2) Under nitrogen atmosphere, 36 mmol of intermediate 1 and 810 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 66.6 mmol of sodium 2-bromoethanesulfonate and 88.2 mmol of triethylamine were added. The mixture was reacted at 55° C. for 36 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and purified by column chromatography (ethyl acetate / petroleum ether 10-50%) to obtain intermediate 2.
[0055] (3) Under nitrogen atmosphere, 32 mmol of intermediate 2 and 1120 mL of dichloromethane were added to a reaction flask. After stirring, 89.5 mmol of boron tribromide was added. The mixture was reacted at 5° C. for 12 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain intermediate 3.
[0056] (4) Under nitrogen atmosphere, 28 mmol of maleic anhydride-modified β-cyclodextrin was added to a reaction flask and dissolved in 980 mL of thionyl chloride. The mixture was stirred at 80° C. for 6 h. The thionyl chloride was removed under reduced pressure. 1200 mL of N,N-dimethylformamide was added and stirred to dissolve. 37.8 mmol of intermediate 3 was added and reacted at 45° C. for 15 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain unsaturated zwitterionic cyclodextrin.
[0057] (5) Under a nitrogen atmosphere, 10 mmol of maleic anhydride, 3.5 mmol of acrylic acid, 2 mmol of unsaturated zwitterionic cyclodextrin and deionized water were added to a microwave reactor. After stirring, 0.12 mmol of ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and the solution was added dropwise at a rate of 0.9 mL / min. After the addition was completed, the solution was reacted at 85° C. for 1.5 h, cooled to 40° C., and a 25% by mass sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0058] Example 5
[0059] (1) Under nitrogen atmosphere, 10 mmol of methoxy polyethylene glycol acrylate and 125 mL of methanol were added to a reaction flask. After stirring, 11.5 mmol of N-methyl-4-methoxybenzylamine was added. The mixture was reacted at 50° C. for 24 h, concentrated under reduced pressure, washed with deionized water, and the organic phase was purified by column chromatography (ethyl acetate / petroleum ether 0-25%) to obtain intermediate 1.
[0060] (2) Under nitrogen atmosphere, 8.5 mmol of intermediate 1 and 205 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 15.3 mmol of sodium 2-bromoethanesulfonate and 22.1 mmol of triethylamine were added. The mixture was reacted at 50° C. for 35 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and purified by column chromatography (ethyl acetate / petroleum ether 10-50%) to obtain intermediate 2.
[0061] (3) Under nitrogen atmosphere, 5 mmol of intermediate 2 and 210 mL of dichloromethane were added to a reaction flask. After stirring, 18 mmol of boron tribromide was added. The mixture was reacted at 0°C for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain intermediate 3.
[0062] (4) Under nitrogen atmosphere, 3 mmol of maleic anhydride-modified β-cyclodextrin was added to a reaction flask and dissolved in 100 mL of dichlorothionyl. The mixture was stirred at 85°C for 8 h. The dichlorothionyl was removed under reduced pressure, 135 mL of N,N-dimethylformamide was added and stirred to dissolve, 5.5 mmol of intermediate 3 was added, and the mixture was reacted at 55°C for 16 h. The mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain unsaturated zwitterionic cyclodextrin.
[0063] (5) Under a nitrogen atmosphere, 10 mmol of maleic anhydride, 3 mmol of acrylic acid, 2.5 mmol of unsaturated zwitterionic cyclodextrin and deionized water were added to a microwave reactor. After stirring, 0.15 mmol of ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and the initiator solution was added dropwise at a rate of 1.2 mL / min. After the addition was completed, the reaction was carried out at 80° C. for 0.52 h, the temperature was lowered to 35° C., and a 30% by mass sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0064] Comparative Example 1
[0065] Under a nitrogen atmosphere, 10 mmol maleic anhydride, 3 mmol acrylic acid, 0.5 mmol maleic anhydride-modified β-cyclodextrin and deionized water were added to a microwave reactor. After stirring evenly, 0.12 mmol ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and added dropwise at a rate of 1 mL / min. After the addition was completed, the reaction was carried out at 85° C. for 1 h, the temperature was lowered to 35° C., and a 25% mass fraction of sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferroferrocement water reducer.
[0066] Comparative Example 2
[0067] (5) Under a nitrogen atmosphere, 10 mmol of maleic anhydride, 3 mmol of acrylic acid, 0.5 mmol of methoxy polyethylene glycol acrylate and deionized water were added to a microwave reactor. After stirring, 0.12 mmol of ammonium persulfate was dissolved in deionized water to prepare an initiator solution, and the initiator solution was added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was reacted at 85° C. for 1 h, cooled to 35° C., and a 25% by mass sodium hydroxide aqueous solution was added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
[0068] Pure paste fluidity test: The Vicat cone method is used to test the pure paste fluidity of cement. Refer to GB / T8077-2023 "Test method for homogeneity of concrete admixtures" to analyze the dispersion performance of water reducer on cement. Pour ferroaluminate cement, water and prepared water reducer into a mixing pot, stir at low speed for 2 minutes, stop stirring for 15 seconds, and then stir rapidly for 2 minutes. Pour the mixed cement paste into a conical test mold quickly, scrape it flat with a scraper, lift the conical test mold in the vertical direction, and wait for the cement paste to flow freely on the glass plane for a certain period of time. The average value of the two diameters obtained in the vertical direction is the pure paste fluidity. The water-cement ratio of ferroaluminate cement is 0.29, and the test temperature is 25°C.
[0069] Table 1 Test of fluidity of pure slurry
[0070]
[0071] From the test results in the above table, it can be seen that with the increase of the content of unsaturated zwitterionic cyclodextrin, the fluidity of the pure slurry of ferroaluminate cement gradually increases, and it has good cement water-reducing and dispersing ability. The fluidity of the cement pure slurry at 120 minutes is still greater than the initial value. This is because on the one hand, the cyclodextrin in the unsaturated zwitterionic cyclodextrin has a hollow cylindrical three-dimensional structure of "narrow on the top and wide on the bottom, hydrophobic inside and hydrophilic outside", which brings a significant steric hindrance effect to the polymer. At the same time, the hydroxyl groups in its structure can form complexes with calcium ions in cement under alkaline conditions, delaying the hydration process of cement and improving the collapse retention ability of the water reducer. On the other hand, the long polyethylene glycol chains in its structure extend radially, and the sulfonic acid groups on the main chain are anchored on the positively charged cement particles, resulting in strong adsorption. The quaternary ammonium salt cations can be adsorbed on the surface of negatively charged cement particles, which enhances the steric hindrance effect, gradually increases the charge density, and enhances the electrostatic repulsion between cement particles. Through the synergistic effect between the various groups, it is easy to adsorb on the surface of cement particles to form a double layer. Under the synergistic steric hindrance of electrostatic repulsion and cyclodextrin and polyethylene glycol long chains, the cement particles can achieve a better dispersion effect and improve the fluidity of cement paste.
[0072] Cement paste setting time test: refer to GB / T 1346-2011 "Test method for water consumption, setting time and stability of cement standard consistency" for testing.
[0073] Table 2 Effect of water reducing agent on cement setting time
[0074]
[0075] With the increase of the content of unsaturated zwitterionic cyclodextrin in the water reducer, the initial and final setting times of ferroaluminate cement are effectively delayed. This is because the presence of cyclodextrin side chains and polyethylene glycol long chains affects the cement hydration process, which can effectively weaken the interpenetration between the water reducer molecules and the clay layer, exert steric repulsion, disintegrate the flocculation structure of cement particles, and make it difficult for the particles to approach each other, so that the polycarboxylate water reducer plays a good role in retarding setting and preventing collapse.
[0076] Cement compressive strength test: Test in accordance with GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)".
[0077] Table 3 Effect of water reducing agent on compressive strength of cement
[0078]
[0079]
[0080] The cyclodextrin molecular chain contains a large number of hydroxyl groups, which can fill the gaps left by the hydration products, thereby enhancing the strength of cement and having a good later strengthening effect on cement mortar. Compared with the traditional method, the method of the present invention has common and easily available raw materials required for the reaction, and the synthesis process is simple, controllable, efficient and convenient, which enriches the preparation method of synthetic ferroaluminate cement water reducer and is easy to realize industrial production.
[0081] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application; the methods used in the present application are conventional methods unless otherwise specified.
Claims
1. A method for preparing a ferroaluminate cement water reducer, characterized in that: The preparation method is carried out according to the following steps: Step (1), under nitrogen atmosphere, add maleic anhydride modified β-cyclodextrin to a reaction flask and dissolve it in dichlorothionyl, stir at 70-85° C. for 3-8 hours, remove dichlorothionyl under reduced pressure, add N,N-dimethylformamide, stir to dissolve, add intermediate 3, react at 40-60° C. for 8-16 hours, cool to room temperature, filter, wash with ethanol, and dry to obtain unsaturated zwitterionic cyclodextrin, the structural formula of intermediate 3 is as follows: Step (2), under a nitrogen atmosphere, maleic anhydride, acrylic acid, unsaturated zwitterionic cyclodextrin and deionized water are added to a microwave reactor, and after stirring evenly, ammonium persulfate is dissolved in deionized water to prepare an initiator solution, and is added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the mixture is reacted at 75-90° C. for 0.5-2 h, cooled to 30-40° C., and a sodium hydroxide aqueous solution is added to adjust the pH to neutral to obtain an alumina-ferrocement water reducer.
2. The method for preparing the ferroaluminate cement water reducer according to claim 1, characterized in that: In the step (1), the molar ratio of maleic anhydride-modified β-cyclodextrin to intermediate 3 is 1:1.5-2.
3. The method for preparing the ferroaluminate cement water reducer according to claim 1, characterized in that: In the step (2), the molar ratio of maleic anhydride, acrylic acid, unsaturated zwitterionic cyclodextrin and ammonium persulfate is 1:0.2-0.4:0.05-0.25:0.008-0.
015.
4. The method for preparing the ferroaluminate cement water reducer according to claim 1, characterized in that: The mass fraction of the sodium hydroxide aqueous solution in step (2) is 20-35%.
5. The method for preparing the ferroaluminate cement water reducer according to claim 1, characterized in that: The preparation method of intermediate 3 in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add methoxy polyethylene glycol acrylate and methanol to a reaction flask, stir evenly, add N-methyl-4-methoxybenzylamine, stir to react, and after the reaction is completed, concentrate under reduced pressure, wash with deionized water, and purify the organic phase by column chromatography to obtain intermediate 1. The structural formula of intermediate 1 is as follows: Step S2, under a nitrogen atmosphere, add intermediate 1 and N,N-dimethylformamide to a reaction flask, stir evenly, add sodium 2-bromoethanesulfonate and triethylamine, react at 40-60° C. for 24-48 hours, extract with ethyl acetate and deionized water, concentrate the organic phase, and purify by column chromatography to obtain intermediate 2, the structural formula of which is as follows: Step S3, under a nitrogen atmosphere, add intermediate 2 and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 0-10°C for 12-24h, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain intermediate 3.
6. The method for preparing the ferroaluminate cement water reducer according to claim 5, characterized in that: In the step S1, the molar ratio of methoxy polyethylene glycol acrylate to N-methyl-4-methoxybenzylamine is 1:(1.05-1.2).
7. The method for preparing the ferroaluminate cement water reducer according to claim 5, characterized in that: In step S1, the reaction temperature is 40-55° C. and the reaction time is 16-24 h.
8. The method for preparing the ferroaluminate cement water reducer according to claim 5, characterized in that: In the step S2, the molar ratio of the intermediate 1, sodium 2-bromoethane sulfonate and triethylamine is 1:(1.5-2.5):(2-3.2).
9. The method for preparing the ferroaluminate cement water reducer according to claim 5, characterized in that: In step S3, the molar ratio of the intermediate 2 to boron tribromide is 1:(2.5-4).
10. A ferroaluminate cement water reducer, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Application of a polycarboxylate water reducer in suppressing side effects of montmorillonite
CN104817663B
Method for synthesizing polycarboxylic acid series cement water reducer accelerated by microwave
CN101186670A
Modified cyclodextrin grafted block polycarboxylic acid water reducer and preparation method thereof
CN114478943A
Cited By
Temperature-sensitive retarder for aluminoferrite cement and preparation method of temperature-sensitive retarder
CN120718210A